Survival and harvest of Atlantic Flyway resident population Canada Geese - Beston, Julie A.; Williams, Christopher K.; Nichols, Theodore C.; Castelli, Paul M. (Wildlife Society Bulletin, 2015)
This article was originally published in Wildlife Society Bulletin. The version of record is available at: https://doi.org/10.1002/wsb.559. © 2015 The Wildlife Society. Resident Population Canada geese (Branta canadensis) are a valuable natural resource, but at high densities they create problems by colliding with vehicles, damaging crops, and fouling parks with feces. Effective management of these geese could be improved with knowledge of demographic rates, especially survival. We used band recovery data from 2005 to 2012 to estimate temporally and spatially explicit survival and recovery rates of Atlantic Flyway Resident Population Canada geese. We analyzed the data in Program MARK and found evidence that survival and recovery varied by age, state of banding, and year. We present state–age–year survival, recovery, and harvest rates from all states. Model-averaged estimates of adult survival ranged from 0.62 to 0.87 and had high precision for most states. Estimates of survival of juvenile geese were generally higher than those for adult geese, but they were less precise and more variable among states. Based on estimates of survival and recovery rates, the average annual harvest rate of adult geese was 13.5% and ranged from 3.1% in North Carolina to 20.1% in Pennsylvania, USA. Harvest rates of juvenile geese were not significantly different from those of adult geese and averaged 15.3%. The estimated survival and harvest rates can be incorporated into population models to assess potential effectiveness of various management strategies for Resident Population Canada geese. © 2015 The Wildlife Society. Funding for this research was provided by the New Jersey Division of Fish and Wildlife, Federal Aid in Wildlife Restoration P-R Grant W-68-R, U.S. Fish and Wildlife Service-Northeast Region, Atlantic Flyway Council, and U.S. Department of Agriculture-Wildlife Services. We thank M. Rogosky at the Bird Banding Lab for providing detailed banding records, J. Fuller for graciously provided Figure 1, the many Canada ...